Agricultural Unrest in the Spanish Transition: The «Days of Struggle in the Countryside» and the Agricultural Protests Wave of 1979-1980 - Redondo Cardeñoso, Jesús Ángel (Hispania Nova, 2023)
This article studies the agricultural unrest that took place in Spain between 1979 and 1980 because of effects of Second Oil Crisis. First, it reviews the evolution of the agricultural movement and protests during the late Franco regime and the first years of the Transition. Afterward, it analyzes the causes, genesis, and development of the agricultural protests between 1979 and 1980, such as the «days of struggle in the countryside» called by COAG (on 27th July 1979, 7th December 1979 and, 4th February 1980), and other regional and provincial protests. The article shows that the agricultural protests during the Spanish Transition did not end after the «Tractor War» of 1977, but also it continued during the following years and was an important part of the peak of social unrest that Spain lived through in 1979.
Keywords: Social unrest; Agricultural Protests; Agricultural Unions; Tractor Blockades; Spanish Transition